Robust fault‐tolerant consensus control for nonlinear multi‐agent systems with prescribed transient and steady‐state performance - Jiang, Yunbiao; Liu, Zhongxin; Chen, Zengqiang (Asian journal of control, 2022)
This paper investigates the finite‐time consensus tracking problem for second‐order nonlinear multi‐agent systems subject to the actuator bias fault. Based on the sliding mode control and prescribed performance control, two distributed fault‐tolerant consensus protocols are proposed for the sudden bias fault and the slowly varying bias fault of the actuator. The first protocol adopts a passive fault‐tolerant control scheme based on the robustness of the system, which has a simple structure, and is timely and effective against sudden faults. In the second protocol, a novel nonlinear recursive sliding mode surface is designed, and a distributed fault observer is proposed to compensate the influences caused by actuator faults actively. Both of the protocols can prescribe the transient and steady‐state performance of the system. Finally, the performances of the two protocols are verified by two simulation cases for the attitude systems of multiple unmanned underwater vehicles.